Predicting Financial Distress on Transportation Company Before and Under Pandemic Covid-19 in Indonesia - Aditya Amanda Pane; Sari Nuzullina Rahmadhani; Hasbiana Dalimunthe (Owner : Riset dan Jurnal Akuntansi, 2022)
Covid-19 pandemic that hit Indonesia had an impact on various lines, including the transportation sector. The social restriction policy as an effort to break the chain of virus spread has the effect of decreasing the ability of transportation companies to maintain their sales. This study aims to determine the tendency of financial distress on transportation companies before and during Covid-19 pandemic. The population in this study are transportation companies listed on Indonesia Stock Exchange. The sampling method used in this research is purposive sampling. With the selected company criterias are people transportation company and the transportation companies have all the data needed in this research. There are 7 transportation companies with quarterly financial report data for 2019-2021. The total data used in this study were each 35 datas before and 35 datas during Covid-19 pandemic. The research method used is Cox Stuart Analysis for Trends to find out trends in the financial distress value. From the research conducted, the results show that 69% of the data shows that companies experienced financial distress before Covid-19 pandemic to 83% experienced financial distress during Covid-19 pandemic, while companies that did not experience financial distress experienced a decrease from 26% before Covid-19 pandemic to 14% during Covid-19 pandemic. The results of the Cox Stuart test show that there is a tendency to decrease the value of altman z-score that indicate an increase in financial distress from 7 transportation companies listed on the IDX before and during Covid-19 pandemic.